Effects of Social Economy, Exclusive Breastfeeding, Complementary Feeding, and Physical Environment on the Stunted Children’s Development - Astari, Rahmi Windhy; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Maternal and infant morbidity and mortality continue to be a challenge today. Most maternal and newborn deaths occur during the early postnatal period. This condition can be caused by low utilization of postnatal care services. This study aims to analyze and estimate the influence of determining factors on the utilization of postnatal care services. Subject and Methods: Meta-analysis was conducted using PRISMA guidelines and PICO format. Population: Postpartum Mothers. Intervention: high antenatal care, high maternal education, high family income and delivery in hospital. Comparison: low antenatal care, low maternal education, low family income, home birth. Outcome: postnatal care services. Cross-sectional study articles were collected from Google Scholar, PubMed, and Science Direct databases. The search strategy used the keywords: